Association between living alone and frailty, and its gender disparity: a multicenter cross-sectional study in Chinese older adults undergoing hospitalisation - Yuanyuan Jiang; Wenbin Wu; Hengshuo Liu; Qi Zhou; Huan Xi (BMC Public Health)
Abstract Background The association between living alone and frailty has not been systematically investigated in previous studies, among which inconsistent results were yielded. This study aimed to understand the association and its gender disparity in Chinese older adults undergoing hospitalisation. Methods This multicenter cross-sectional study included 1037 older adults aged 65 years or older. Comprehensive geriatric assessment was performed to collect information. Frailty was assessed using the FRAIL scale and the Fried Frailty Phenotype (FFP) criteria. Sociodemographic features were obtained through questionnaires. Depression was evaluated with the 2-item Patient Health Questionnaire (PHQ-2), and anxiety was evaluated with the 2-item Generalized Anxiety Disorder Questionnaire (GAD-2). Activities of daily living, chronic diseases and multimorbidity were systematically assessed by healthcare professionals. The association between living alone and frailty was investigated using logistic regression models, with potential confounders adjusted for. Results 171 (16.5%) older adults were living alone. The overall prevalence of frailty was 19.4% and 17.4% according to the FRAIL scale and the FFP criteria, respectively. Older adults who were living alone had a higher prevalence of frailty (28.7% by FRAIL and 24.4% by FFP) than those who were living with others (17.6% by FRAIL and 16.0% by FFP) (P < 0.01 for both criteria). Living alone was significantly associated with frailty in logistic regressions (FRAIL, OR = 1.89, 95% CI = 1.30–2.75; FFP, OR = 1.70, 95% CI = 1.13–2.53). The association was significant only in males (FRAIL: male, OR = 2.55, 95% CI = 1.55–4.21; female, OR = 1.30, 95% CI = 0.73–2.32). Similar results were observed in fully adjusted models that controlled for age, marital status, and morbidity status. Conclusions For Chinese older patients, living alone is a marker of risk for frailty, especially for men. Assessing living arrangements as an indicator to identify older inpatients at elevated risk of frailty could help guide targeted screening and supportive care.